Water and wastewater engineering design principles and practice - Davis, Mackenzie L (McGraw-Hill, 2010)
Fundamental environmental engineering principles are used as the foundation for rigorous design of conventional and advanced water and wastewater treatment processes. Integrating theory and design, this title follows the flow of water through a water treatment plant and the flow of wastewater through a wastewater treatment plant.